2022
DOI: 10.1007/s40264-022-01159-2
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Machine Learning-Based Decision Support for Signal Validation Classification

Abstract: Introduction Signal validation in pharmacovigilance is the process of evaluating data to decide whether evidence is sufficient to justify further assessment of a detected signal. During the signal validation process, safety experts in our organization are required to review signals of disproportionate reporting (SDRs) and classify them into one of six predefined categories. Objective This experiment explored the extent to which predictive machine learning (ML) models ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For instance, ‘reported causality’ (i.e., the availability of information on single-case causality assessments in structured fields) was one of the least frequent features. However, this feature was described as helpful in a decision-support system for signal validation when SDRs were confounded by indication [ 19 ]. To facilitate a critical interpretation of signals, judgments on features of ADR reports may be made clearer in clinical assessments (e.g., [ 20 , 21 ]).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ‘reported causality’ (i.e., the availability of information on single-case causality assessments in structured fields) was one of the least frequent features. However, this feature was described as helpful in a decision-support system for signal validation when SDRs were confounded by indication [ 19 ]. To facilitate a critical interpretation of signals, judgments on features of ADR reports may be made clearer in clinical assessments (e.g., [ 20 , 21 ]).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that recent papers can be classified into three types of databases, namely clinical [13], [18], [27], [33], registry [10], [12], [20], [24], [25], [29], [34], and knowledge [14], [15], [16], [17], [19], [21], [22], [23], [26], [28], [30], [31], [32], [35]. Additionally, based on review papers of existing XAI models [48], [49], the XAI algorithms used were divided into the following four categories: surrogate The main advantage of an explanatory technique such as SHAP is that it has solid roots in game theory, which ensures that the explanation of a prediction instance is fairly distributed across the features.…”
Section: ) Xai Methodsmentioning
confidence: 99%
“…Moreover, the emergence of additional data sources such as biochemical databases, electronic health records (EHRs), insurance claims or other "Real-World Data" (RWD) and social media (Hussain, 2021; Knowledge Base workgroup of the Observational Health Data Sciences and Informatics (OHDSI) collaborative, 2017) have led to relevant research initiatives (Natsiavas et al, 2019b;Ball et al, 2022). To this end, Machine Learning (ML) algorithms are also under investigation (Lee et al, 2022;Imran et al, 2022), including the use of Natural Language Processing (NLP) which is elaborated to identify ADR mentions in EHRs/clinical notes or other free text/unstructured data. Other Knowledge Engineering approaches (e.g., the use of Semantic Web technologies, ontologies and "reasoning" upon Knowledge Graphs etc.)…”
Section: Introductionmentioning
confidence: 99%